Menggali Keunikan Cerita Anak melalui Bedah Buku bersama Forum Lingkar Pena Sumbar - Syafrina, Dewi (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2025)
Book reviews (Bedah Buku) are not only useful for criticizing someone's work, but also for increasing the reader's understanding of the book. Book reviews are one of the important post-reading activities to be carried out in order to be a bridge between the book and its readers. We carry out this activity so that the author and reader get the meaning of the book discussed from a different perspective. Using the discussion method, the book review activity that we carried out together with the Lingkar Pena Forum explored the uniqueness and shortcomings of the children's story book Kaka si Istimewa and Pesan Bapak Rangga. This activity can train the reader's critical thinking and also appreciate the work that has been produced by the author.